Epitaxial germanium deposited by MOVPE on InGaAs quantum dot stressors grown by MBE. Issue 8 (28th April 2014) - Bosi, M.; Attolini, G.; Frigeri, P.; Nasi, L.; Rossi, F.; Seravalli, L.; Trevisi, G.
<x xml:space="preserve">Abstract</x> We studied the deposition at different temperatures of Ge layers by on InGaAs quantum dots. The structures were characterized by Photoluminescence and Atomic Force Microscopy before and after Ge epitaxy. Cross sectional Transmission Electron Microscopy shows that the Ge overlayer is epitaxially grown on the InGaAs/GaAs QD underlayer, with the same orientation. No structural defects are observed in the structures. Intermixing and In desorption occurs at higher deposition temperature. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>